2017
DOI: 10.1371/journal.pone.0182306
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolutionary patterns of NAD+/Sirtuin aging signaling pathway across taxa

Abstract: A deeper understanding of the conserved molecular mechanisms in different taxa have been made possible only because of the evolutionary conservation of crucial signaling pathways. In the present study, we explored the molecular evolutionary pattern of selection signatures in 51 species for 10 genes which are important components of NAD+/Sirtuin pathway and have already been directly linked to lifespan extension in worms and mice. Selection pressure analysis using PAML program revealed that MRPS5 and PPARGC1A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Recent work on the comparative genomics of the p53 molecular network provided evidence of positive selection on genes within p53 networks of reptile (both ecto-and endothermic) relative to mammals, with reptiles having more positive selection on upstream genes (p53 and its regulators), especially in lizards and snakes (Passow et al, 2019). This is in contrast to the purifying selection on p53 across mammals (Gaur et al, 2017;Passow et al, 2019), with the exception of the branch leading to elephants (Passow et al, 2019). We also found that species with longer lifespans experienced less variation in selection across the p53 network, whereas those with shorter lifespans were equally likely to have both positive and purifying selection (Passow et al, 2019).…”
Section: Molecular Network For Cellular Senescence: P53/p16mentioning
confidence: 99%
“…Recent work on the comparative genomics of the p53 molecular network provided evidence of positive selection on genes within p53 networks of reptile (both ecto-and endothermic) relative to mammals, with reptiles having more positive selection on upstream genes (p53 and its regulators), especially in lizards and snakes (Passow et al, 2019). This is in contrast to the purifying selection on p53 across mammals (Gaur et al, 2017;Passow et al, 2019), with the exception of the branch leading to elephants (Passow et al, 2019). We also found that species with longer lifespans experienced less variation in selection across the p53 network, whereas those with shorter lifespans were equally likely to have both positive and purifying selection (Passow et al, 2019).…”
Section: Molecular Network For Cellular Senescence: P53/p16mentioning
confidence: 99%
“…Past research has identified evidence of positive selection across genes and pathways associated with apoptosis and cancer in mammals (Crespi and Summers 2006; Kosiol et al. 2008; Gaur et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, treating AD with mTOR as the target, the timing of medication may be a crucial factor. Furthermore, the side effects of rapamycin and its analogue cannot be ignored, like reduced fertility and impaired locomotor activity [86]. Additionally, further research is needed to examine the beneficial effects of rapamycin in AD flies before deciding whether it can be a potential drug for clinical treatment of AD.…”
Section: Mtor Signaling Pathwaymentioning
confidence: 99%